Credit Booms, Debt Overhang and Secular Stagnation - Gerhard Illing; Yoshiyasu Ono; Matthias Schlegl (Center for Economic Studies and ifo Institute (CESifo), 2017)
Why do advanced economies fall into prolonged periods of economic stagnation, particularly in the aftermath of credit booms? We present a model of persistent aggregate demand shortage based on strong liquidity preferences of households, in which we incorporate financial imperfections to study the interactions between debt, liquidity and asset prices. We show that financially more deregulated economies are more likely to experience persistent stagnation. In the short run, credit booms can mask this structural aggregate demand deficiency. However, the resulting debt overhang permanently depresses spending in the long run since deleveraging becomes self-defeating because of debt deflation. These findings are in line with the macroeconomic developments in Japan during its lost decades and other advanced economies before and during the Great Recession.
Keywords: E41; 330; secular stagnation; aggregate demand deficiency; liquidity preferences; financial frictions. leverage